The characteristics of knee pain and associated socio- demographic factors among the patients attending the Orthopedic clinic in Teaching Hospital Jaffna - Illangasinghe, I.M.T.M.; Zakee, S.M.; Kamalarupan, L.; Gobyshanger, T. (University of Jaffna, 2024)
Background: Knee pain is a prevalent musculoskeletal symptom across all age groups, significantly impacting daily activities and quality of life. Various risk factors are associated with knee pain. Objective: This study aims to evaluate the characteristics of knee pain and its association with socio-demographic factors among patients attending the Orthopedic Clinic at Teaching Hospital, Jaffna. Methodology: A descriptive cross-sectional study was conducted among 426 patients experiencing knee pain. Participants were selected using a systematic random sampling method from the orthopedic clinics. Data collection was done with an interviewer- administered questionnaire. Ethical clearance was obtained from the Ethical Review Committee, Faculty of Medicine, University of Jaffna. Data analysis was performed using SPSS 20, with the severity of knee pain assessed using a numerical pain scale (Mild: 1-3, Moderate: 4-6, Severe: 7-10). Chi-square tests and univariate analysis were employed to determine associations and describe knee pain characteristics, respectively. Results: The participants' ages ranged from 19 to 93 years, with a mean age of 58.47 years (SD=14.832). The majority were females (59.4%) and Sri Lankan Tamils (96.7%). Most participants earned between 5000 and 10000 Sri Lankan Rupees per month (48.8%), with 29.6% earning less than 5000 Sri Lankan Rupees per month. The highest level of education for most participants was up to the Ordinary level (48.6%). The majority (91.8%) reported moderate or severe pain, with around half of them experiencing knee pain bilaterally (50.2%). Statistically significant relationships were observed between the severity of knee pain and various socio-demographic factors, including age, gender, per capita monthly income, educational level, type of occupation, and daily work activities. Conclusion: The majority of participants reported moderate or severe knee pain, which was significantly associated with various socio-demographic factors. Recommendations include advising the target population to avoid prolonged standing or sitting with knee flexion based on their occupation.
Keywords: Knee Pain; Orthopedic Patients; Orthopedic Clinic; Teaching Hospital Jaffna